PENGEMBANGAN POTENSI EKSTRAK KULIT BUAH RAMBUTAN SEBAGAI BAHAN OBAT HERBAL ANTIHIPERKOLESTEROL - . Muhtadi; . Haryoto; Tanti Azizah Sujono; Peni Indaryudha; Andi Suhendi (Biomedika, 2013)
The rind of rambutan fruit (Nephelium lappaceum L.) has been reported to have a very strong antioxidant activity with IC50 value of 7.74 μg / mL. The fruit contains  avonoids and phenolic . This compounds are potentially as hypolipidemic effect. This study aims to determine the hypolipidemic effect of 96% of ethanolic extract of rind of rambutan fruit in wistar strain male rats. This research method is the pre- and post-control group design. 25 rats were divided into 5 groups. Group I (negative control) were treated by a solution of 0.5% CMC-Na, group II (positive control) were treatedby cholestyramine 0.8 kg / kg, whereas group III, IV and V treated by 96% of ethanolic extract of rind of rambutan with a dose of 125 , 250, and 500 mg / kg respectively. hiperkolesterlemia induction is done by giving a high cholesterol diet and feed for 4 weeks. High-cholesterol diet consists of cooking oil, quail egg yolk, water, PTU and feed high cholesterol consisting of margarine and standard feed. Treatment of mice was conducted for 2 weeks. The results showed that the 96% of ethanolic extract of rind of rambutan fruit with a dose of 125, 250, and 500 mg / kgbw have antihyperkolesterol activity 21.39 ± 6.61%, 31.15 ± 18.15%, and 60.75 ± 8, 26%.Keywords: Antihypercholestrol, Nephelium Lappaceum L., High-cholesterol diet